PERANCANGAN DAN PEMBUATAN MEJA CAFE MULTIFUNGSI YANG ERGONOMIS BAGI PELANGGAN DI EXCELSO CAFE DP MALL SEMARANG - Mutiara Sari, 08.04.51.0012 Ayu (Students Journal of Engineering, 2013)
Customer convenience in Excelso Cafe DP Mall in Semarang are still not fully realized because of the facilities that still does not meet ergonomic criteria that the customer used the cafe table. Ergonomics of a product or work facilities that will be used / operated by humans is extremely important in order to meet the criteria for an effective, comfortable, safe, healthy and efficient (ENASE). Excelso cafe table on ergonomic yet due to high base aligned with the table so quickly cause physical fatigue on the user / customer. In addition, extensive desk duty felt less comfortable because it has a dimension of size L x W x H = 50 cm x 50 cm x 45 cm. So the customer feel less free when using the table. The application of ergonomic design is an activity or facility in making the product more convenient to use. The design was done by determining the size of the human body dimensions. One method that can be used to determine the size of the dimensions of the human body is due to an anthropometric studies related to the measurement of the dimensions of every human body. Anthropometric methods are applied in measuring the dimensions of the bodys activities are aimed at a table for customers Excelso Cafe DP Mall in Semarang. Meanwhile, to determine the level of comfort on the table produced, performed deployment questionnaire where the results will be tested its validity by conducting validity and reliability. Based on the data obtained from the results of research in Excelso Cafe DP Mall in Semarang for the ergonomic design of the cafe tables in order to improve customer convenience size calculation results obtained in a more ergonomic table desk is 71 cm long, 71 cm wide table and table height 72 cm. Â  Keywords: Product Design, Ergonomics, Multifunction Table Cafe